Rational Design of New Monoterpene-Containing Azoles and Their Antifungal Activity - Nikolai S. Li-Zhulanov; Nadezhda P. Zaikova; Suat Sari; Dolunay Gülmez; Suna Sabuncuoğlu; Keriman Ozadali-Sari; Sevtap Arikan-Akdagli; Andrey A. Nefedov; Tatyana V. Rybalova; Konstantin P. Volcho; Nariman F. Salakhutdinov (MDPI AG, 2023)
Azole antifungals, including fluconazole, have long been the first-line antifungal agents in the fight against fungal infections. The emergence of drug-resistant strains and the associated increase in mortality from systemic mycoses has prompted the development of new agents based on azoles. We reported a synthesis of novel monoterpene-containing azoles with high antifungal activity and low cytotoxicity. These hybrids demonstrated broad-spectrum activity against all tested fungal strains, with excellent minimum inhibitory concentration (MIC) values against both fluconazole-susceptible and fluconazole-resistant strains of Candida spp. Compounds 10a and 10c with cuminyl and pinenyl fragments demonstrated up to 100 times lower MICs than fluconazole against clinical isolates. The results indicated that the monoterpene-containing azoles had much lower MICs against fluconazole-resistant clinical isolates of Candida parapsilosis than their phenyl-containing counterpart. In addition, the compounds did not exhibit cytotoxicity at active concentrations in the MTT assay, indicating potential for further development as antifungal agents.